Percepción de la situación socioprofesional inicial del futuro titulado/a en pedagogía. - Joseph Mafokozi (Universidad Complutense de Madrid, 2006)
This study analyzes several aspects related with future educators' perceptions concerning the studies they are about to finish as well as their expectations with relation to the society and the labor market. The obtained results draw a panorama in which a future educator appears like a professional lacking of trust as for the technical capacity acquired along his/her education. Similarly he/she considers scarce the level of knowledge that the society and the labor world has of his/her professional offer. However, this perception does not favor an active attitude of personal involvement in the creation of a specific professional space.